2021
DOI: 10.3390/ijerph18020749
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Agreement between Physicians and a Consultation–Liaison Psychiatry Team at a General Hospital: An Exploratory Study across 20 Years of Referrals

Abstract: Consultation–liaison psychiatry (CLP) manages psychiatric care for patients admitted to a general hospital (GH) for somatic reasons. We evaluated patterns in psychiatric morbidity, reasons for referral and diagnostic concordance between referring doctors and CL psychiatrists. Referrals over the course of 20 years (2000–2019) made by the CLP Service at Modena GH (Italy) were retrospectively analyzed. Cohen’s kappa statistics were used to estimate the agreement between the diagnoses made by CL psychiatrist and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…Together, they accounted for 56.41% of the total number of consultations. These results were consistent with those reported previously, both in China and worldwide, which indicates that somatic symptoms were the primary reason for a hospital visit among most of the patients with depressive disorder or anxiety disorder [10,23,24]. Recently, it has been observed that mild, rather than severe, mental disorder has become the most common type of psychiatric disease diagnosed upon consultation in general hospitals.…”
Section: Psychia Tric Consultation Diagnosissupporting
confidence: 91%
See 1 more Smart Citation
“…Together, they accounted for 56.41% of the total number of consultations. These results were consistent with those reported previously, both in China and worldwide, which indicates that somatic symptoms were the primary reason for a hospital visit among most of the patients with depressive disorder or anxiety disorder [10,23,24]. Recently, it has been observed that mild, rather than severe, mental disorder has become the most common type of psychiatric disease diagnosed upon consultation in general hospitals.…”
Section: Psychia Tric Consultation Diagnosissupporting
confidence: 91%
“…In addition to the high rate of incidence of depressive or anxiety disorders, and the probability of those being comorbidities with physical disorders, our study also demonstrated that greater attention is being paid to psychological factors. This was not limited only to severe mental disorders, but was also observed for mild mental disorders [10,19,23,25,26].…”
Section: Psychia Tric Consultation Diagnosismentioning
confidence: 65%
“…More than half of the requested psychiatric consultations were related to disease diagnosis. Consultationliaison (CL) psychiatry has been indicated as a valuable strategy for mental care in patients admitted to general hospitals because of somatic reasons (22,23). Immediate diagnosis and treatment of psychiatric disorders in patients hospitalized due to physical illnesses can improve the treatment of co-occurring somatic disorders, reduce the length of hospital stay, and relieve economic and health complications (7,10).…”
Section: Discussionmentioning
confidence: 99%
“…Mood and anxiety disorders were the most frequently diagnosed psychiatric problems. An exploratory study on 18,888 referrals to CL psychiatrists during 20 years (2000 -2019) at a general hospital in Italy reported depression and agitation as the most common reasons for psychiatric consultation (22). A review conducted by Hosseini et al showed that mood disorders and substance use were the most frequent mental problems identified through psychiatric consultations in general hospitals (2).…”
Section: Discussionmentioning
confidence: 99%
“…[8] Studies of diagnostic concordance between referring physicians and psychiatrists are mostly retrospective, and delirium was usually studied amongst other psychiatric disorders. Though prevalence varies across types of hospital wards, delirium is among the top three most common conditions in patients diagnosed by C/L psychiatrists, together with major depression and adjustment disorder, [9][10][11] and is first in geriatric [9] or critically ill patients, such as those undergoing liver transplantation. [12] However, concordance between diagnoses made by medical/ surgical referring physicians and C/L psychiatrists is quite low (Kappa indexes 0.2-0.4 or concordance around 40%).…”
Section: Introductionmentioning
confidence: 99%